PETROGRAPHY OF PYROCLASTIC ROCK MOUNT MASURAI JAMBI PROVINCE - Kirana, Febiyora Chandra; Nuriil Tadersi, Risnaliyah; Hasbullah, Andrea; Siregar, Anggi Deliana; Ritonga, D.M Magdalena; Utama, Hari Wiki; Misnawati, Misnawati (Prodi Fisika FST UNJA, 2024)
The magmatic arc of Sumatra Island, which is indicated by the presence of the Barisan Mountains zone on the west side of Sumatra Island with a general direction northwest - southeast, makes Mount Masurai, which is administratively in Merangin Regency, Jambi Province, become one of the volcanoes on Sumatra Island. Geographically, the peak of Mount Masurai is located at coordinates 101o 51' 28.60